GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASI SEBAGAI PEMODERASI PENGARUH PARTISIPASI ANGGARAN PADA KESENJANGAN ANGGARAN - Prawita, Widya; Pradnyantha Wirasedana, I Wayan (E-Jurnal Akuntansi; Vol 19 No 1 (2017), 2017)
Budget is a statement regarding the estimation of the performance to be achieved during certain period of time stated in the financial measures. The purpose of this study are determine the effect of budget participation to budget slack with leadership style and organizational commitment as a moderating variable. This study was conducted at the Plantation Office of Bali Province. Samples were obtained by 32 people using probably sampling with judgment sampling techniques. Data collected through questionnaires. Data analysis technique is moderated regression analysis. Based on the analysis found that budgetary participation variable positive influence on budgetary slack. These results indicate that the higher participation will given the opportunity to create their own standards to judge their performance, and will have tendency to use their knowledge to create slack. Leadership style strengthen the influence of budgetary participation on budgetary slack. Organizational commitment weaken the influence of budgetary participation on budgetary slack.
Keywords: budget participation, budgetary slack, leadership style, organizational commitment